2019
DOI: 10.3390/f10030272
|View full text |Cite
|
Sign up to set email alerts
|

Amazon Fund 10 Years Later: Lessons from the World’s Largest REDD+ Program

Abstract: Results-Based Funding (RBF) for Reducing Emissions from Deforestation and Forest Degradation (REDD+) has become an important instrument for channeling financial resources to forest conservation activities. At the same time, much literature on conservation funding is ambiguous about the effectiveness of existing RBF schemes. Many effectiveness evaluations follow a simplified version of the principal-agent model, but in practice, the relation between aid providers and funding recipients is much more complex. As … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
(78 reference statements)
0
34
0
1
Order By: Relevance
“…Alternatively, by assuming that only 56% of the decline in deforestation could be attributed to the government's efforts, as suggested in the literature (Assunção et al, 2015;Cunha et al, 2016), the value of the avoided deforestation would be USD 4.1 ± 1.1 billion. In both cases, these estimates far exceed the current amount of USD 1.2 billion donated to the Amazon Fund to support forest conservation and sustainable development activities in the country (Correa et al, 2019). We note that these values only refer to emissions from deforestation and do not necessarily capture the impacts of forest degradation from logging and associated facilitation of forest fires and biological invasions by lianas, bamboos, or pioneer tree species (e.g., Vidal et al, 2016;Tyukavina et al, 2017;Aragão et al, 2018).…”
Section: Biomass and Carbon-stock Uncertaintiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Alternatively, by assuming that only 56% of the decline in deforestation could be attributed to the government's efforts, as suggested in the literature (Assunção et al, 2015;Cunha et al, 2016), the value of the avoided deforestation would be USD 4.1 ± 1.1 billion. In both cases, these estimates far exceed the current amount of USD 1.2 billion donated to the Amazon Fund to support forest conservation and sustainable development activities in the country (Correa et al, 2019). We note that these values only refer to emissions from deforestation and do not necessarily capture the impacts of forest degradation from logging and associated facilitation of forest fires and biological invasions by lianas, bamboos, or pioneer tree species (e.g., Vidal et al, 2016;Tyukavina et al, 2017;Aragão et al, 2018).…”
Section: Biomass and Carbon-stock Uncertaintiesmentioning
confidence: 91%
“…The fund was designed to raise and manage donations for the promotion of actions aligned with the PPCDAm's goals to prevent, mitigate, and monitor deforestation, as well as to promote forest conservation and sustainable use of natural resources (Brazil, 2016). To date, the fund has raised over USD 1.2 billion in donations, mainly from the government of Norway, with smaller amounts from Germany and Petrobras (the Brazilian semi-public petroleum industry; Correa et al, 2019). In exchange for the donations, the Amazon Fund issues certificates of avoided carbon emissions from deforestation, which are nominal and non-transferable (Brazil, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…For REDD+, this implies comparing result-based payments from carbon funds and markets for forest managers at the end of the policy's time frame, compared to the costs incurred, by using a cost-benefit analysis of REDD+ initiatives. Correa et al [32] detail the allocation of financial resources from the USD 667 million Brazilian Amazon fund across different stakeholders for scientific and technological development, sustainable production, monitoring and control, and land tenure regularization. However, in terms of the forest conservation effectiveness, as well as emissions reductions from deforestation, they found that deforestation rates had risen since 2013, despite increased fund disbursements.…”
Section: Policy Effectivenessmentioning
confidence: 99%
“…For REDD+, this implies the analysis of outputs (such as a single REDD+ project), outcomes (for example, behavioral changes of forest managers due to REDD+ initiatives), and/or impacts (such as an increase of carbon sequestration and carbon stocks in a forest) in a specific landscape. Correa et al [32] attribute the apparent lack of effectiveness to the distribution mechanism of the Brazilian Amazon fund that prioritized diverse organizations rather than a strategic selection of projects due to its predetermined theory of change. Rosa da Conceição et al [42] looked at REDD+ in Ecuador and Peru and the pathways of two government-led, incentive-based forest conservation and poverty reduction programs for forest-based populations.…”
Section: Policy Outputs Outcomes and Impactsmentioning
confidence: 99%
See 1 more Smart Citation